The affective affordances of frugal science using foldscopes during a Life Sciences water quality practical - Cherine Jackson; Josef de Beer; Lounell White (Perspectives in Education, 2020)
Manu Prakash, the developer of the foldscope microscope reported on in this paper, stated that it is important to use tools that can support open-ended inquiry in the classroom, without dumbing down those tools. Scientific equipment in the school laboratory is often very expensive and only available to those who can afford it. “Frugal science” is a trend in education that researches, develops and introduces economical and quality scientific resources to developing countries. In South Africa, many underprivileged schools lack quality practical and laboratory resources to perform simple tasks, such as microscopy. Furthermore, the absence of laboratory investigations could lead to learners not enjoying Life Sciences nor developing a more nuanced understanding of the nature (tenets) of science. As part of an indigenous knowledge intervention hosted by the North-West University, teachers were provided with $1 foldscopes (paper microscope) to use in their classrooms. This research reports on the views of Life Sciences learners and teachers on the use of foldscopes in the Life Sciences classroom during a practical lesson. The focus of the research is to illuminate how such problem-based approaches could enhance affective outcomes. This generic qualitative research study has elements of design-based research (DBR) as well as classroom action research (CAR), carried out by participating teachers to investigate the affordances of foldscopes. Data was collected using observations, teacher reflections, learner reflections, photographs and personal interviews. From an affective stance, this qualitative study used Engeström’s third-generation Cultural-Historical Activity Theory (CHAT) as a research lens in order to identify factors that promote or inhibit the use of foldscopes in the Life Sciences classroom during a practical lesson.